The Legal Basis for Subjecting Revenue Derived from Intellectual Property Rights to Income Tax - Anwar Noori Khaleel; Raid Naji AHMED (Revista Jurídica Portucalense)
International treaties concluded by Iraq and comparable countries regarding the prevention of double taxation and tax evasion, which include provisions on the tax treatment of intellectual property rights, serve as an international legal foundation. States are obligated to adhere to the provisions of these treaties and agreements, despite the varying legal status they hold in relation to other legal norms, as determined by the constitution of each country. Most constitutions grant treaties and agreements a legal status equivalent to legislation, treating them as subsequent legislation that overrides earlier laws, as seen in Iraq, Jordan, and Egypt. In other cases, such as in France, these treaties are accorded a higher legal status than domestic legislation. Accordingly, Iraq is required to comply with the tax treaties it has concluded and the international agreements it has joined, particularly those that include provisions on the tax treatment of intellectual property rights. This obligation persists even if domestic tax legislation does not explicitly impose taxes on such rights, as demonstrated by the practices of Egypt and Jordan. France has taken this principle further, holding that in cases of conflict between its treaties and domestic legislation, the provisions of the treaties take precedence. This is because the country is internationally bound to impose taxes on intellectual property rights under these agreements, and failure to do so would constitute a breach of its international obligations.